PERANAN KOMPETENSI PENDIDIK DAN MEDIA PEMBELAJARAN DALAM MEMOTIVASI BELAJAR PESERTA DIDIK PROGRAM STUDI PENDIDIKAN AGAMA KRISTEN - Susilo, David Priyo (Shift Key : Jurnal Teologi dan Pelayanan, 2017)
This study discusses the competence of educators,  learning media and its relationship  with learning motivation learners.  Researchers  have a longing, "Educators  on the study program 'Christian  Religious Education' in STT 'Christ Alfa Omega' Semarang" can achieve the vision of STT is, "Being the School of Theology of Excellence and Biblical Characterized Pentakosta  Kharismatik". One of the achievement targets is "Superior Educator".  The superiority of educators is the superiority in improving the competence and use of instructional  media. The advantage  of learners  is to have the motivation to learn. The method used in this research  is quantitative descriptive method, the number of respondents 20 people. The result of the research  by showing the level of competence of educator and learning media in motivating the students of study program "Christian  Education" is 94% or in very good category, but there are two things that need to be improved that educators are expected to be role models and educators can increase media usage learning so as to foster enthusiasm in learning.